PROSEDUR TEST OF CONTROL TERHADAP SALDO KAS DAN SETARA KAS PT MPS OLEH KANTOR AKUNTAN PUBLIK PAUL HADIWINATA, HIDAJAT, ARSONO, RETNO, PALILINGAN DAN REKAN - Lutfi Muzhaffar Syakir (2023)
Test of Control (TOC) is a procedure used to evaluate the effectiveness and reliability of internal controls in an organization. The purpose of this study is to understand the concept and importance of TOC in maintaining the integrity and reliability of the internal control system. Performing TOC on cash and cash equivalent accounts is an important matter for the Public Accounting Firm, therefore in the process of testing controls (Test of Control) it must first create a TOC plan to achieve good implementation of control tests in accordance with professional auditor regulations. In testing the controls for cash and cash equivalent account balances, the authors had the opportunity to conduct audit tests on PT MPS, which is a client of KAP Paul Hadiwinata, Hidajat, Arsono, Retno, Palilingan and Partners engaged in manufacturing. Procedures for testing controls of PT MPS include preparing table assertions related to TOC, identifying, and understanding internal controls, testing documentation, conducting interviews with relevant personnel, vouching for TOC cash and cash equivalent accounts. By conducting a test of control, the auditor can evaluate whether the internal controls implemented by the entity are effective or not, and whether they can deal with existing risks effectively or not. In this case, the auditor can determine the appropriate audit method and determine the extent to which internal control can produce correct and reliable accounting information. The results of this test of control will be used by the auditor to plan further audit actions, including substantive testing.